Total Phenolic Content and In vitro Antioxidant Activity of Winged Bean (Psophocarpus tetragonolobus) - Khalili, R. Mohd Adzim; Shafekh, S. Emynur; Norhayati, A.H.; Fatahudin, I. Mohd; Rahimah, R.; Norkamaliah, H.; Azimah, A. Nor (Pakistan Journal of Nutrition, 2013)
Psophocarpus tetragonolobus also known as the Asparagus pea or winged pea (Family: Fabaceae) most widely grown in hot, humid equatorial countries like Malaysia. It provides a source of vitamin A, vitamin C, calcium and iron. The antioxidant potential of 75% methanol extract, ethyl acetate and chloroform soluble fractions of P. tetragonolobus was screened for in-vitro antioxidant activity using total phenolic content, ferric reducing power, 2, 2’-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay, Ferric Thiocyanate (FTC) and Thiobarbituric Acid (TBA) tests. It was found that ethyl acetate fraction have maximum amount of polyphenolics compounds (1.69 mg/g GAE in concentration 0.5 mg/mL) higher than methanol and chloroform fractions. Antioxidant concentration was found highest in ethyl acetate extract (27.12 mM) using FRAP method, while chloroform extract has the highest antioxidant level (4.48 mM) using ABTS assay. Ethyl acetate extract of P. tetragonolobus was found to have highest antioxidant activity (7.27%) compared to methanol and chloroform using FTC method. While, TBA results shows no difference in antioxidant activity of all extract of P. tetragonolobus.